(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Uterine fibroid is most common solid benign tumors in women of reproductive age. The symptoms of uterine fibroid adversely affect social and recreational activities, women’s quality of life, and productivity at work. Uterine fibroid occur in 50–60% of women, rising to 70% by the age of 50 and in 30% of cases cause morbidity. A 40-year-old married woman consulted in the outpatient department (OPD) of P.G. department of Prasutitanta and Striroga with a complaint of heavy and prolong menstrual bleeding with painful menstruation since 5 years. It is associated with lower back pain, lower abdominal pain, frequent urination, mild constipation and pain in both lower extremities. Her Ultrasonography report shows bulky uterus and intramural uterine fibroid size of 19x17x25 mm. Patient was treated according to Ayurvedic management of Granthi. So the drug having properties Raktstambhak, Lekhana, Raktshodhak, Shothahara, etc. are used with advice of Pathya Aahar-Vihara.Treatment was continued for one years with a follow up once in 15days and a repeat scan revealed shrinking size of the fibroid and relief in all symptoms.